Eucalyptus ESTs associated with resistance to herbicide inhibitors of aromatic and branched-chain amino acid synthesis - Velini, Edivaldo Domingues [UNESP]; Trindade, Maria Lúcia Bueno [UNESP]; Alves, Elza [UNESP]; Catâneo, Ana Catarina [UNESP]; Marino, Celso Luis [UNESP]; de Godoy Maia, Ivan [UNESP]; Mori, Edson Seizo [UNESP]; Furtado, Edson Luiz [UNESP]; Guerrini, Iraê Amaral [UNESP]; Wilcken, Carlos Frederico [UNESP] (FapUNIFESP (SciELO), 2005)
Herbicides inhibit enzymatic systems of plants. Acetolactate synthase (ALS, EC = 4.1.3.18) and 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS, EC 2.5.1.19) are key enzymes for herbicide action. Hundreds of compounds inhibit ALS. This enzyme is highly variable, enabling the selective control of weeds in a number of crops. Glyphosate, the only commercial herbicide inhibiting EPSPS is widely used for non-selective control of weeds in many crops. Recently, transgenic crops resistant to glyphosate were developed and have been used by farmers. The aim of this study was the data mining of eucalypt expressed sequence tags (ESTs) in the FORESTs Genome Project database (https://forests.esalq.usp.br) related to these enzymes. Representative amino acid sequences from the NCBI database associated with ALS and EPSPS were blasted with ESTs from the FORESTs database using the tBLASTx option of the blast tool. The best blasting reads and clusters from FORESTs, represented as nucleotide sequences, were blasted back with the NCBI database to evaluate the level of similarity with available sequences from different species. One and seven clusters were identified as showing high similarity with EPSPS and ALS sequences from the literature, respectively. The alignment of EPSPS sequences allowed the identification of conserved regions that can be used to design specific primers for additional sequencings. Copyright by the Brazilian Society of Genetics.
Keywords: ALS; EPSPS; Eucalyptus; Herbicides; 3 phosphoshikimate 1 carboxyvinyltransferase; acetolactate synthase; aromatic amino acid; branched chain amino acid; glyphosate; herbicide; agricultural worker; amino acid sequence; amino acid synthesis; controlled study; crop; data base; enzyme inhibition; expressed sequence tag; FORESTs Genome Project database; GenBank; gene cluster; herbicide resistance; information processing; nonhuman; nucleotide sequence; transgenic plant; weed control